An interval multiobserver for nonlinear systems subject to internal and external disturbances: Real time experimental validation. (August 2022) - Fida, Tahri; Samah, Ben Atia; Anis, Messaoud; Ridha, Ben Abdennour
Abstract: The present work focuses on the design of an interval multiobserver for nonlinear systems with internal and external disturbances. The structure of the developed interval multiobserver is based on a discrete uncoupled multimodel. The used multimodel is known for its flexibility in the modeling step, since the state variables of the partial models can evolve in state spaces with different dimensions. Sufficient stability conditions are formulated in terms of linear matrix inequalities (LMIs), and nonnegativity constraints are imposed to ensure the cooperativity dynamic of the observation errors. A numerical example and an experimental validation on an esterification reactor are given to prove the significance of the proposed interval multiobserver. Highlights: This paper deal with the design of an interval multiobserver for nonlinear systems with internal and external disturbances. The structure of the developed interval multiobserver is based on a discrete uncoupled multimodel. Sufficient stability conditions are formulated in terms of linear matrix inequalities (LMIs), and nonnegativity constraints are imposed in order to ensure the cooperativity dynamic of the observation errors.